The Clinical Characteristics of Obese Patients with Acanthosis Nigricans and Its Independent Risk Factors - Huang, Yueye; Chen, Jiaqi; Wang, Xingchun; Li, Yan; Yang, Shezhen; Qu, Shen (Experimental and Clinical Endocrinology & Diabetes, 2017)
Objective: This study aimed to investigate the clinical characteristics and risk factors for acanthosis nigricans (AN) in obese patients.Methods: 80 obese patients without AN (OB group) and 128 obese patients with AN (AN group) were included in this study. Clinical data for each patients were collected. Serum levels of leptin were measured by ELISA.Results: Body mass index (BMI), uric acid (UA) levels, fasting insulin, and HOMA-IR were higher in AN than OB (P<0.05). The levels of leptin were significantly higher in AN than OB (P<0.001) after adjustment for BMI and gender. In male patients, AN showed lower serum levels of testosterone than OB (P<0.001). Multiple Logistic-regression analysis demonstrated that UA (OR 4.627, 95%CI 2.443–8.762, P<0.001) and Leptin (OR 4.098, 95%CI 1.237–13.581, P=0.021) were independent risk factors for AN. In addition, low testosterone level was an independent risk factor for AN in male obese patients (OR 39.062, 95%CI 5.523–283.808, P<0.001).Conclusions: AN is associated with more severe hyperinsulinemia and hyperuricemia in obese patients, as well as lower serum testosterone levels in male patients. UA and Leptin were independent risk factors for AN in obese patients. Low testosterone may be a valuable predictor of AN in male obese patients.
Keywords: obesity; acanthosis nigricans; insulin resistance; leptin; testosterone